Inclusion of Murder News in the Posmetro Padang Daily Newspaper: A Study of Critical Discourse Analysis - Fitri, Rahayu; Rahmat, Wahyudi (Humaniora, 2017)
The purposes of this research were to describe the marginalized of the murder news and the process of inclusion of the murder news in the Posmetro Padang daily newspaper. The research applied a descriptive qualitative method. The object of this research was the inclusion strategy of the murder news in the paper. This occurred through three strategies; they were the differentiation strategy, objectivation-abstraction, and assimilation-individualization. The results of this research are the most journalists of murder news in Posmetro Padang daily newspaper try impartially and the perpetrators, as if the offender is a party that is good and right, while those who fall victim as a marginalized and regarded as the bad news. The inclusion of seven murders news that has been analyzed and published in the Posmetro Padang daily newspaper.